Electric vehicle drive system with adaptive PID control - Couceiro, Micael S. (2010)
The aim of this work is to implement an adaptive PID SISO feedback control to obtain a fine adjustment of an electric vehicle (EV) driving system. Our research work is done under different operating conditions, namely, variable battery voltage and variable load. A comparison between conventional and adaptive PID algorithms is established when they are applied to the above mentioned conditions. Experimental results indicate that the adaptive PID controller leads to a faster response and a better stability. Furthermore, the adaptive PID controller follows a given reference velocity faster and more smoothly than the conventional PID controller.